Biomechanical modelling of paralympic wheelchair curling - Laschowski, B. (University of Waterloo, 2013)
This research represents the first documented investigation into the biomechanics and neural motor control of Paralympic wheelchair curling. A multibody biomechanical model of the wheelchair curling delivery was developed in reference to a Team Canada Paralympic athlete with a spinal cord injury. Subject-specific body segment parameters were quantified via dual-energy x-ray absorptiometry. The angular joint kinematics throughout the wheelchair curling delivery were experimentally measured using an inertial measurement unit system; the translational kinematics of the curling stone were additionally evaluated with optical motion capture. The experimental kinematics were optimized to satisfy the kinematic constraints of the multibody biomechanical model. The optimized kinematics were subsequently used to compute the resultant joint moments through inverse dynamics analysis. The neural motor control of the Paralympic athlete was modeled using forward dynamic optimization. The predicted kinematics from different optimization objective functions were compared with those experimentally measured throughout the wheelchair curling delivery. Of the optimization objective functions under consideration, minimizing angular joint accelerations resulted in the most accurate predictions of the kinematic trajectories and the shortest optimization computation time. The implications of these findings are discussed in relation to musculoskeletal modeling and optimal equipment design through predictive simulation.